International Legal Aspects of Energy Security - A. A. Kovalev; N. L. Shilova (Московский журнал международного права, 2008)
The article covers essential legal aspects of international (global) energy security, based on the analysis of Energy Charter Treaty (1994) and G-8 summits documents. The balance between producers and consumers of energy and transit countries, energy efficiency and ecological aspects are the key issues for international energy security today. The Energy Charter Treaty provides a tangible contribution in the area of global energy security. Treaty’s binding mechanisms for investments protection and the issues of reliability of transit as well as the operations’ transparency of energy markets are designed to provide the international energy security. New energy players, China and India, should be involved into the cooperative dialogue on energy. One more aspect is to ensure that policies pursued by governments and international organizations provide the sustainable energy future.